Silencing of the Aspergillopepsin B (pepB) Gene of Aspergillus awamori by Antisense RNA Expression or Protease Removal by Gene Disruption Results in a Large Increase in Thaumatin Production - Moralejo, Francisco J.; Cardoza, Rosa Elena; Gutierrez, Santiago; Lombraña, Marta; Fierro, Francisco; Martín, Juan F. (Applied and Environmental Microbiology, 2002)
Classifications Services AEM Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue AEM About AEM Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy AEM RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0099-2240 Online ISSN: 1098-5336 Copyright © 2014 by the American Society for Microbiology. For an alternate route to AEM .asm.org, visit: AEM